1
$\begingroup$

I need help with this:

"Find all functions $f$, $g : \mathbb{Z} \rightarrow \mathbb{Z}$, with $g$ injective and such that: $$f(g(x)+y) = g(f(x)+y), \mbox{ for all } x, y \in \mathbb{Z}.$$

$\endgroup$
  • $\begingroup$ Did you mean all functions? $\endgroup$ – Julien Feb 13 '13 at 18:46
  • $\begingroup$ italic bold YES $\endgroup$ – user62189 Feb 13 '13 at 19:20
  • 1
    $\begingroup$ A few random remarks: Notice that if we set $y=0$, we get $f(g(x))=g(f(x))$ for every $x\in\mathbb{Z}$. $f$ is injective: we can write every $x\in\mathbb{Z}$ as $g(0) + y$ for some $y = y(x)\in\mathbb{Z}$, and thus $f(x) = f(g(0) + y) = g(f(0)+y)$, and both $g$ and $y$ are injective. If there is some $x\in\mathbb{Z}$ with $n = f(x) = g(x)$, then we have $f(n+k)=f(g(x)+k)=g(f(x)+k)=g(n+k)$, and thus $f = g$. In this case, any injective $f:\mathbb{Z}\rightarrow\mathbb{Z}$ solves the problem, by setting $g=f$. $\endgroup$ – Daniel Robert-Nicoud Feb 13 '13 at 20:21
3
$\begingroup$

Suppose $f,g:\Bbb Z\to\Bbb Z$ with $g$ injective and $$f(g(x)+y)=g(f(x)+y)\tag{#}$$ for all $x,y\in\Bbb Z$.

Note that $$f(0)=f(g(x)-g(x))=g(f(x)-g(x))\tag{1}$$ for all $x$, so since $g$ is injective, then $f(x)-g(x)$ is constant. In particular, then $$f(x)=g(x)+c\tag{2}$$ for some $c\in\Bbb Z$. Note that it then follows that $f$ is injective.

It follows from $(1)$ and $(2)$ that $$g(c)=g(f(x)-g(x))=f(0)=g(0)+c.$$ Suppose $g(x+c)=g(x)+c$ for some $x\in\Bbb Z$. Then $$g(x+1+c)=g(f(0)-g(0)+x+1)=f(g(0)-g(0)+x+1)=f(x+1)=g(x+1)+c,$$ and similarly, $$g(x-1+c)=g(x-1)+c.$$ By $2$-directional induction on $x$, we have $$g(x+c)=g(x)+c\tag{3}$$ for all $x\in\Bbb Z$. Using $(3)$, another quick $2$-directional induction on $m$ will show that $$g(y+mc)=g(y)+mc\tag{4}$$ for all $m,y\in\Bbb Z.$

Now, if $c=0$, then we must have $f=g$ by $(2)$. Suppose $c\neq 0$. Given any $x\in\Bbb Z$, there is a unique $0\leq y<|c|$ such that $x=y+mc$ for some $m\in\Bbb Z$ (why?)--denote this $y$ by $r(x)$--so by $(4)$, we have $$g(x)=g(r(x)+mc)=g(r(x))+mc=g(r(x))+x-r(x),$$ so $$g(x)-x=g(r(x))-r(x).$$ Defining $h(x):=g(x)-x$, we have $$h(x)=h(r(x))\tag{5}$$ for all $x\in\Bbb Z$. Observing that $r(x+mc)=r(x)$ for all $x,m\in\Bbb Z$ (why?), it follows that $h$ is a periodic function $\Bbb Z\to \Bbb Z$, with $c$ a period of $h$.


The above gives us necessary conditions for $f,g$ to satisfy. We will see that they are sufficient, as well. Specifically, we prove the following:

Claim: Suppose $f,g:\Bbb Z\to\Bbb Z$ with $g$ injective. Then $f,g$ satisfy $(\#)$ if and only if one of the following holds:

(a) $f=g$, or

(b) there is some non-$0$ $c\in\Bbb Z$ and some periodic function $h:\Bbb Z\to\Bbb Z$ such that $h$ has $c$ as a period, $g(x)=h(x)+x$, and $f(x)=g(x)+c$ for all $x\in\Bbb Z$.

Proof: We saw above that if $f,g$ satisfy $(\#)$, then (a) or (b) holds. If (a) holds, then it's easily seen that $f,g$ satisfy $(\#)$, so suppose that (b) holds. Then $$\begin{align}f(g(x)+y) &= g(g(x)+y)+c\\ &= h(g(x)+y)+g(x)+y+c\\ &= h(g(x)+y+c)+g(x)+y+c\\ &= g(g(x)+y+c)\\ &= g(g(x)+c+y)\\ &= g(f(x)+y),\end{align}$$ as desired. $\Box$

$\endgroup$
0
$\begingroup$

How about $f(x)=g(x)=x?$......

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.